Field-relevant doses of the systemic insecticide fipronil and fungicide pyraclostrobin impair mandibular and hypopharyngeal glands in nurse honeybees (Apis mellifera) - Zaluski, Rodrigo [UNESP]; Justulin, Luis Antonio [UNESP]; Orsi, Ricardo De Oliveira [UNESP] (Springer Nature, 2017)
Global decreases in bee populations emphasize the importance of assessing how environmental stressors affect colony maintenance, especially considering the extreme task specialization observed in honeybee societies. Royal jelly, a protein secretion essential to colony nutrition, is produced by nurse honeybees, and development of bee mandibular glands, which comprise a reservoir surrounded by secretory cells and hypopharyngeal glands that are shaped by acini, is directly associated with production of this secretion. Here, we examined individual and combined effects of the systemic fungicide pyraclostrobin and insecticide fipronil in field-relevant doses (850 and 2.5 ppb, respectively) on mandibular and hypopharyngeal glands in nurse honeybees. Six days of pesticide treatment decreased secretory cell height in mandibular glands. When pyraclostrobin and fipronil were combined, the reservoir volume in mandibular glands also decreased. The total number of acini in hypopharyngeal glands was not affected, but pesticide treatment reduced the number of larger acini while increasing smaller acini. These morphological impairments appeared to reduce royal jelly secretion by nurse honeybees and consequently hampered colony maintenance. Overall, pesticide exposure in doses close to those experienced by bees in the field impaired brood-food glands in nurse honeybees, a change that could negatively influence development, survival, and colony maintenance.